Pengalaman Tamu sebagai Tolok Ukur Kualitas Layanan : Studi Kualitatif pada Hotel Bintang Empat di Bali - Jeanny Pricilia Anneke W; Fadillah Manuhutu (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2025)
This study aims to explore guest experience as a benchmark for service quality in four-star hotels in Bali. Using a qualitative phenomenological approach, the research was conducted at two representative hotels, namely Four Points by Sheraton Bali, Kuta and The Anvaya Beach Resort Bali. Data were collected through semi-structured in-depth interviews with 20 guests who had stayed for at least one night within the past six months, online review analysis from platforms such as Booking.com and TripAdvisor, as well as participatory observations in service areas.The findings reveal that the dimensions of service quality most influencing guest experience include staff responsiveness, facility comfort, and the authenticity of services that integrate local culture. Guests appreciated staff friendliness and professionalism, room cleanliness, and personal touches such as being greeted by name or receiving special attention, which created positive emotional experiences. However, several weaknesses were also identified, such as delays in room service during peak hours and inconsistent maintenance of facilities. These results are consistent with the SERVQUAL model (Parasuraman et al., 1988), which emphasizes five key dimensions, but this study highlights the emotional experience dimension, which has been less explored in hospitality research in Bali. This study makes a theoretical contribution by broadening the understanding of the relationship between service quality and guest experience, particularly in the context of four-star hotels that are characterized by high service standards and intense competition. The practical implications suggest that hotel management should strengthen service personalization, ensure consistency in staff reliability and responsiveness, and enhance the integration of local cultural values as a differentiation strategy to increase competitiveness. Thus, guest experience can serve as a primary indicator that not only reflects service quality but also builds customer loyalty and strengthens the hotel’s positive image among both domestic and international tourists.